Prognostic Value of S100 Family mRNA Expression in Hepatocellular Carcinoma - Wan, Renrui; Tan, Zhenhua; Qian, Hai; Li, Peng; Zhang, Jian; Zhu, Xiaofeng; Xie, Ping; Ren, Lingyan (Turkish Journal of Gastroenterology, 2024)
Background/Aims: The S100 family contains more than 20 Ca2+-binding proteins that participate in numerous cellular biological processes. However, the prognostic value of individual S100s in hepatocellular carcinoma (HCC) remains unclear. Therefore, we comprehensively assessed the prognostic value of S100s in HCC. Materials and Methods: The mRNA level of S100s in distinct types of cancer was analyzed through Oncomine. The clinical prognostic significance of each S100 was evaluated using Kaplan–Meier plotter and OncoLnc. The expression and mutation of S100s were determined through cBioPortal. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes analyses were used to predict the functions and pathways of S100s. Results: The analyses revealed that, relative to normal tissues, liver cancer tissues showed aberrant mRNA expression of most S100s. In the survival analysis with Kaplan–Meier plotter, elevated expression levels of S100PBP, S100A2, S100A7, S100A10, and S100A13 were related to shorter overall survival (OS), whereas increased S100A5 expression was associated with longer OS. Moreover, results obtained using OncoLnc showed that increased expression levels of S100P, S100PBP, S100A13, S100A11, S100A10, and S100A2 were related to shorter OS. Thus, S100PBP, S100A13, S100A10, and S100A2 exhibited the same prognostic trend in the 2 databases. However, all S100 member gene mutational changes had no considerable prognostic value in OS and disease-free survival of HCC patients. Conclusion: Although the findings need to be further confirmed by experiments, they provide new evidence for the prognostic significance of the S100s in HCC Cite this article as: Wan R, Tan Z, Qian H, et al. Prognostic value of S100 family mRNA expression in hepatocellular carcinoma. Turk J Gastroenterol. 2024;35(4):316-334.